Voyages autour de la Méditerranée : pour une approche géopoétique de L’immoraliste et Si le grain ne meurt d’André Gide - Bors, Edit (Verbum – Analecta Neolatina, 2020)
L’immoraliste (1902) and Si le grain ne meurt (1921) by Gide are both based on the narratives of travel and the quest for the self that describe the protagonist’s experiences and sensations while visiting the Mediterranean Basin (from Tunis to Sorrente, through Sousse, Biskra, Syracuse, Ravello, etc.) Each leg of the trip creates a sensation of joy and fulness which transforms the traveller’s interior life and shows him the deeper meaning of his existence. The purpose of the paper is to define the relation between descriptive writing techniques and Mediterranean aesthetics. We aim to examine how the perception and description of geographical areas in which the spiritual seeking take place reflect the psychological development of the protagonist.